2013
DOI: 10.1620/tjem.231.281
|View full text |Cite
|
Sign up to set email alerts
|

Poor-Quality Sleep Is Associated with Metabolic Syndrome in Korean Adults

Abstract: Sleep disorder and metabolic syndrome (MetS) are important health-related problems. Recently, sleep duration has decreased among Korean adults. In this study, we examined whether sleep quality is associated with MetS by analyzing 301 subjects, aged 20 years or over, without acute and severe illness who visited three primary care clinics. Sleep duration, sleep quality and the risk of sleep-related breathing disorder (SRBD) were assessed with a standardized sleeping-estimating instrument. MetS was defined accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…The located publications in turn confirmed statistically significant associations between LDL-C or HDL-C and poor quality sleep (4)(5)(6) . At the same time, the located studies were carried out principally among adults, the elderly or middle-aged people.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The located publications in turn confirmed statistically significant associations between LDL-C or HDL-C and poor quality sleep (4)(5)(6) . At the same time, the located studies were carried out principally among adults, the elderly or middle-aged people.…”
Section: Discussionmentioning
confidence: 62%
“…There is still no conclusive biologically plausible explanation for this, or even for any relationship between sleep and lipid profile. Conjectures exist, such as: individuals with the habit of spending longer in bed (longer duration sleep) are more sedentary and/or overweight than others, inevitably entailing high lipid levels (4)(5)(6) .…”
Section: Introductionmentioning
confidence: 99%
“…A total of 18 studies (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39) were selected for inclusion in this metaanalysis. Table E4 outlines the characteristics of study participants.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies (28)(29)(30)35) reported MetS using the Third Report of the National Cholesterol Education Program (NCEP) Expert Panel on Detection, Evaluation, and Treatment of High Blood Cholesterol in Adults (ATP-III) (40). Three studies (24,37,39) reported MetS using the NCEP/ATP III …”
Section: Resultsmentioning
confidence: 99%
“…Subjects with sleep apnea have significantly more possibilities to develop MS and cardiovascular pathology [11]. On the other hand, MS is associated with poor quality of sleep [12], and with excessive daytime sleepiness [13]. For example, Chang et al [14] identified a high prevalence of calcified atheromas in patients with syndrome Z.…”
Section: Comparison With Other Studies and Explanationsmentioning
confidence: 99%